2000
DOI: 10.1016/s0924-9338(00)94877-6
|View full text |Cite
|
Sign up to set email alerts
|

P03.472 Prognosis of remission in paranoid schizophrenic patients

Abstract: 450s Posters, Tuesday, 3 I October 2000 stressors was in better correlation with subsequent posttraumatic pathology than it was exposure alone. Conclusion:Our results have shown that our Scale of Exposure and Distress could contribute to a better evaluation of the interrelations between intensity, frequency and subjective reactions to stressors and posttraumatic pathology in population exposed to ,different categories of traumatic experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Researchers from Moscow still submitted a majority of the abstracts, although psychiatrists from St. Petersburg, Tomsk, Novosibirsk, Kaluga, Kemerovo, and other cities and from some former Soviet republics (Ukraine, Kazakhstan, Azerbaijan) were represented. The studies of schizophrenia presented mainly continued to elaborate phenomenology and course (Alimkhanov 1996; Ismailov and Ismailov 1996; Mazaeva and Abramova 1996; Panteleeva and Dikaya 1996; Platonova 1996; Tiganov 1996; Zaltsman 1996), although some other topics included neuropsychological, immunologic, neuroimaging (computed tomography [CT], group therapy, rehabilitation, psychopharmacology, genetic, and family studies (Alfimova and Trubnikov 1996; Golovina and Mazaeva 1996; Govorin et al 1996; Loginovich 1996; Nuller 1996; Semke 1996; Vasil’eva et al 1996 a ; Zhankov 1996). New topics for Russian psychiatry covered in the abstracts included the economics of care, statistics, legal issues, analysis of risk and benefit of care, quality assurance of psychiatric care, and analysis of trends in current Russian psychiatry in relation to the history of abuses of psychiatry (Dmitrieva 1996; Gluzman 1996; Kazakovtsev 1996; Prokudin 1996; Rytik 1996; Savenko 1996; Shevchenko 1996; Solokhina 1996; Yastrebov et al 1996).…”
Section: The History Of Russian-soviet Psychiatry: Development Of The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers from Moscow still submitted a majority of the abstracts, although psychiatrists from St. Petersburg, Tomsk, Novosibirsk, Kaluga, Kemerovo, and other cities and from some former Soviet republics (Ukraine, Kazakhstan, Azerbaijan) were represented. The studies of schizophrenia presented mainly continued to elaborate phenomenology and course (Alimkhanov 1996; Ismailov and Ismailov 1996; Mazaeva and Abramova 1996; Panteleeva and Dikaya 1996; Platonova 1996; Tiganov 1996; Zaltsman 1996), although some other topics included neuropsychological, immunologic, neuroimaging (computed tomography [CT], group therapy, rehabilitation, psychopharmacology, genetic, and family studies (Alfimova and Trubnikov 1996; Golovina and Mazaeva 1996; Govorin et al 1996; Loginovich 1996; Nuller 1996; Semke 1996; Vasil’eva et al 1996 a ; Zhankov 1996). New topics for Russian psychiatry covered in the abstracts included the economics of care, statistics, legal issues, analysis of risk and benefit of care, quality assurance of psychiatric care, and analysis of trends in current Russian psychiatry in relation to the history of abuses of psychiatry (Dmitrieva 1996; Gluzman 1996; Kazakovtsev 1996; Prokudin 1996; Rytik 1996; Savenko 1996; Shevchenko 1996; Solokhina 1996; Yastrebov et al 1996).…”
Section: The History Of Russian-soviet Psychiatry: Development Of The...mentioning
confidence: 99%
“…Vasil’ieva et al (1996 b ) reported improvement in the functional activity of natural killers (NK) and T-helper cells (TH) in response to treatment with neuroleptics in 25 patients with schizophrenia. At the 10th World Congress of Psychiatry (1996), Russian researchers were overrepresented in the section on psychoneuroimmunology focusing on immunological changes as an indicator of treatment response (Domashneva et al 1996; Ismailov 1996), HLA-antigens as markers for various types of treatment resistance (Govorin et al 1996), and immunological changes in different types and stages of schizophrenia (Ismailov 1996; Sekirina et al 1996).…”
Section: The Russian Concept Of Schizophreniamentioning
confidence: 99%